Tocilizumab Use among Patients Who Developed Pulmonary Embolism in the Course of Cytokine Release Storm and COVID-19 Pneumonia—A Retrospective Study - Daniel Chober; Bogusz Aksak-Wąs; Jolanta Niścigorska-Olsen; Małgorzata Niekrasz; Miłosz Parczewski (Biomedicines, 2022)
Introduction: Thromboembolic events, including mainly pulmonary embolisms and ischemic strokes, occur in up to one-third of COVID-19 patients. As efficacy of tocilizumab (TCZ) among patients with acute pulmonary embolism (PE) was not previously investigated, this study aimed to provide such data. Objectives: The aim of the study was to investigate the effect of TCZ on mortality in patients with confirmed acute pulmonary embolism, cytokine release storm and COVID-19 pneumonia. Patients and methods: Longitudinal data of 4287 patients with confirmed SARS-CoV-2 infection were collected between 4 March 2020 and 16 January 2022. In this study, we retrospectively analyzed the samples and dataset of cases with confirmed acute pulmonary embolism associated with at least moderate lung involvement due to COVID-19 pneumonia. Results: In the analyzed dataset, 64 adult patients were diagnosed with PE, and of these, 28 (44%) cases were treated with two 8 mg/kg doses of TCZ, and 36 (56%) did not receive this agent. The groups were balanced regarding demographics, comorbidities and the biochemical markers. Overall mortality in our study was 29.6% (n = 17). Mortality in the group treated with TCZ was 43% (n = 12) compared to 19% (n = 7) in the group without TCZ. In multivariate proportional Cox hazards models, intravenous administration of TCZ was independently associated with higher mortality (HR: 3.342 (CI: 1.077–10.370), p = 0.036). Conclusions: In patients with COVID-19 pneumonia with at least moderate lung involvement, CRS and acute pulmonary embolism, administration of TCZ is associated with increased mortality. Therefore, TCZ should be used with caution in SARS-CoV-2 cases with pulmonary embolism.